Estado nutricional e mortalidade entre pacientes idosos transferidos para unidade de cuidados intensivos : uma coorte retrospectiva - Andreo, Francilene Oliveira (2020)
Introduction: Many patients need to be transferred for procedures, or because they require more complex care. However, the transfer may have worse outcomes. Objective: to compare the nutritional status and mortality of elderly patients transferred to ICU with those admitted to the ICU from their residence. Method: Retrospective cohort carried out in a private hospital in the city of Cuiabá-MT. Study carried out with elderly patients admitted to two ICUs. The frequency of patients transferred to the ICU was determined and then nutritional status and mortality were compared between transferred patients versus those admitted directly to ICU. A patient referred from any unit of the hospital itself (intra-hospital) or when referred from the ward of another hospital (inter-hospital) to the ICU was considered a hospital transfer. Results: Among 2190 hospitalized patients, 60.0% (n=1315) were elderly who participated in the study (mean=73 years, 53.1% female). The transfer rate corresponded to 26.8% of the cases. The transferred elderly were 2.5 times more likely to die than those admitted directly to the ICU (OR=2.55, 95%CI1.91-3.39, p<0.001) and were more likely to be severely malnourished than those from house (OR=2.5 95%CI 1.82-3.4), p<0.001). The chance of death increased only among the transferred elderly who were already malnourished (OR= 2.9; p<0.001) or severely malnourished (OR= 3.2; p<0.001) at the time of admission to the ICU. The same did not occur for those directly admitted (p>0.05). Conclusion: About 30% of patients admitted to the ICU are from hospital transfers. The transferred elderly are more malnourished than those admitted directly to the ICU. Transferred elderly and those transferred with malnutrition are more than 2.5 times more likely to die than those directly admitted with or without malnutrition.